A Case of Cervical Intraneural Lipoma That Was Removed by Intercapsular Resection with No Resultant Postoperative Neurological Deficit. (20th June 2022) - Sato, Hitoshi; Saito, Yoshiro; Kitajima, Tatsuya; Egawa, Shunya; Shimane, Toshikazu
Abstract : Intraneural lipomas in peripheral nerves of cervical lesions are extremely rare and have not been previously reported. We present a 48-year-old male with a gradually increasing right cervical mass since 5 years. He visited our department because of pain and difficulty in raising the right upper limb. A tumor about 80 mm in size was palpable in the right neck along the cervical nerve. The tumor was suspected to involve fatty degeneration in schwannoma of cervical nerve origin, for which intercapsular resection was performed under general anesthesia. Histopathologically, bifurcated growth of mature adipocytes with sparse fibrous septa and lack of tumor proliferation of Schwann cells was observed on H&E staining, suggesting a diagnosis of intraneural lipoma. The patient had no new motor or sensory deficits postoperatively and with improvement in his preoperative symptoms.